Individualizing Fluid Management in Patients with Acute Respiratory Distress Syndrome and with Reduced Lung Tissue Due to Surgery-A Narrative Review - Benes, Jan; Kasperek, Jiri; Smekalova, Olga; Tegl, Vaclav; Kletecka, Jakub; Zatloukal, Jan (Journal of personalized medicine, 2023)
Fluids are the cornerstone of therapy in all critically ill patients. During the last decades, we have made many steps to get fluid therapy personalized and based on individual needs. In patients with lung involvement-acute respiratory distress syndrome-finding the right amount of fluids after lung surgery may be extremely important because lung tissue is one of the most vulnerable to fluid accumulation. In the current narrative review, we focus on the actual perspectives of fluid therapy with the aim of showing the possibilities to tailor the treatment to a patient's individual needs using fluid responsiveness parameters and other therapeutic modalities.
Keywords: hemodynamics; thoracic surgery; fluids; fluid responsiveness; acute respiratory distress syndrome